2017
DOI: 10.18632/oncotarget.21661
|View full text |Cite
|
Sign up to set email alerts
|

Genetic predisposition toward suicidal ideation in patients with acute coronary syndrome

Abstract: The genetic predisposition toward suicidal ideation has been explored to identify subgroups at high risk and to prevent suicide. Acute coronary syndrome (ACS) is associated with an increased risk of suicide, but few studies have explored the genetic predisposition toward suicide in ACS populations. Therefore, this longitudinal study explored the genetic predisposition toward suicidal ideation in ACS patients. In total, of 969 patients within 2 weeks after ACS, 711 were followed at 1 year after ACS. Suicidal id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…In relation to stressful life events, individuals with one or two copies of the short allele exhibited more depressive symptoms and suicidality than subjects homozygous for the long allele. This observation was confirmed by Kang et al who demonstrated that the short allele may cause a genetic predisposition toward suicidal ideation in patients 2 weeks after an acute coronary syndrome (Kang et al 2017). While a meta-analysis found no evidence of a strong interaction between stress and the 5-HTTLPR genotype contributing to the development of depression (Culverhouse et al 2018), one study demonstrated effects of environmental stress and gender on associations among depressive symptoms and the 5-HTTLPR genotype (Brummett et al 2008a).…”
Section: Introductionmentioning
confidence: 81%
“…In relation to stressful life events, individuals with one or two copies of the short allele exhibited more depressive symptoms and suicidality than subjects homozygous for the long allele. This observation was confirmed by Kang et al who demonstrated that the short allele may cause a genetic predisposition toward suicidal ideation in patients 2 weeks after an acute coronary syndrome (Kang et al 2017). While a meta-analysis found no evidence of a strong interaction between stress and the 5-HTTLPR genotype contributing to the development of depression (Culverhouse et al 2018), one study demonstrated effects of environmental stress and gender on associations among depressive symptoms and the 5-HTTLPR genotype (Brummett et al 2008a).…”
Section: Introductionmentioning
confidence: 81%
“…stress and frustration in life) (Aaltonen et al, 2016;Zhang et al, 2016;Buckner et al, 2017). From a biological perspective, abnormalities in the serotonergic (5-hydroxytryptamine, 5-HT) system (Picouto et al, 2015), dysregulation of the hypothalamicpituitary-adrenal axis (Ghaziuddin et al, 2014), and a genetic contribution (Kang et al, 2017) to the risk of suicide have been found. Based on neuroimaging perspective, the present study observed that the left DLPFC GMV reductions as a biological factor may play a role in suicidal ideation in depression.…”
mentioning
confidence: 99%
“…Some studies report different results such as an association of the lower expressing serotonin transporter S allele or S/S genotype of 5-HTTLPR polymorphism with extreme criminal behavior in Chinese male prisoners 76 and violent behavior in adult German criminal offenders with history of childhood ADHD 77 . Other studies also reported association of S allele or S/S genotype with antisocial alcoholism 78 , concussion history and personality traits in rugby players 79 , suicidal ideation in acute coronary syndrome patients 80 , higher impulsivity, hostility and neuroticism in anxiety phenotype 81 , hyperactivity-impulsivity in children moderated by peer problems earlier in childhood 82 and increased exposure to life stressors moderated by ADHD symptoms early in life 83 . Some meta-analyses also describe association of low expression allele/genotype of 5-HTTLPR polymorphism with anti-social behavior 84 , violent suicide attempts 85 and bipolar disorder 86 .…”
Section: Discussionmentioning
confidence: 93%